Autoimmunity and Cytokine Imbalance in Inherited Epidermolysis Bullosa - Esposito, Susanna (Int J Mol Sci, 2016)
In order to evaluate the serum anti-skin autoantibodies and cytokine concentrations in patients with different epidermolysis bullosa (EB) types and severity, 42 EB patients and 38 controls were enrolled. Serum anti-skin antibodies were significantly higher in the patients than in the controls (p = 0.008, p < 0.001, p < 0.001, p < 0.001 and p < 0.001 for desmoglein 1 (DSG1) desmoglein 3 (DSG3), bullous pemphigoid 180 (BP180), BP230 and type VII collagen (COL7), respectively). The same trend was observed for interleukin (IL)-1β, IL-2, IL-6, IL-10, tumor necrosis factor-β, and interferon-γ (p < 0.001, p < 0.001, p < 0.001, p = 0.008, p < 0.001 and p = 0.002, respectively). Increases in anti-skin antibodies and cytokine concentrations were higher in patients with recessive dystrophic EB than in those with different types of EB, in generalized cases than in localized ones, and in patients with higher Birmingham Epidermolysis Bullosa Severity (BEBS) scores than in those with a lower score. The BEBS score was directly correlated with BP180, BP230, COL7 (p = 0.015, p = 0.008 and p < 0.001, respectively) and IL-6 (p = 0.03), whereas IL-6 appeared significantly associated with DSG1, DSG3, BP180, BP230 and COL7 (p = 0.015, p = 0.023, p = 0.023, p = 0.015 and p = 0.005, respectively). This study showed that autoimmunity and inflammatory responses are frequently activated in EB, mainly in severe forms, suggesting the use of immunosuppressive drugs or biologicals that are active against pro-inflammatory cytokines to reduce clinical signs and symptoms of disease.